Answer:
3r^2 /2
Step-by-step explanation:
r^3 cancels out r in the denominator remaining with r^2 in the numerator.
so 3r^2/2
= 3r^2 /2
STEP 1- since 6 doesn't contain the variable to solve for move it to the right side of the equation by subtracting 6 from both sides
X^2-8X=-6
STEP 2- create a trinomial square on the left side of the equation find the value that is equal to the square of half of b the coefficient of x
(b/2)^2 =(-4)^2
STEP 3- add the term to each side of the equation
x^2-8x+(-4)^2=-6=(-4)
STEP 4- simplify the equation
x^2-8x+16=10
STEP 5- factor the perfect trinomial square into (x-4)^2
(x-4)^2=10
STEP 6-solve the equation for x
x=4= square root of 10
there are many combinations for it, but we can settle for say
![\bf \begin{cases} f(x)=x+2\\[1em] g(x)=\cfrac{9}{x^2}\\[-0.5em] \hrulefill\\ (f\circ g)(x)\implies f(~~g(x)~~) \end{cases}\qquad \qquad f(~~g(x)~~)=[g(x)]+2 \\\\\\ f(~~g(x)~~)=\left[ \cfrac{9}{x^2} \right]+2\implies f(~~g(x)~~)=\cfrac{9}{x^2}+2](https://tex.z-dn.net/?f=%5Cbf%20%5Cbegin%7Bcases%7D%20f%28x%29%3Dx%2B2%5C%5C%5B1em%5D%20g%28x%29%3D%5Ccfrac%7B9%7D%7Bx%5E2%7D%5C%5C%5B-0.5em%5D%20%5Chrulefill%5C%5C%20%28f%5Ccirc%20g%29%28x%29%5Cimplies%20f%28~~g%28x%29~~%29%20%5Cend%7Bcases%7D%5Cqquad%20%5Cqquad%20f%28~~g%28x%29~~%29%3D%5Bg%28x%29%5D%2B2%20%5C%5C%5C%5C%5C%5C%20f%28~~g%28x%29~~%29%3D%5Cleft%5B%20%5Ccfrac%7B9%7D%7Bx%5E2%7D%20%5Cright%5D%2B2%5Cimplies%20f%28~~g%28x%29~~%29%3D%5Ccfrac%7B9%7D%7Bx%5E2%7D%2B2)
Answer:
52.9
Step-by-step explanation:
Multiply 67 by .79
Answer:
Its THIS ↓↓↓↓
Step-by-step explanation:
if its not this then i dk what